PENGEMBANGAN MEDIA PEMBELAJARAN ELEKTRONIK MENGGUNAKAN EDMODO DALAM MENINGKATKAN PEMAHAMAN KONSEP PELAJARAN EKONOMI - Zainal, Zainal; Asriati, Nuraini; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Â AbstractThis research was conducted at SMAN 1 Sambas, the aim of this research were to develop electronic learning media using edmodo; analyze the feasibility of learning media and to analyze the effectiveness of learning media using edmodo in improving students' concept comprehension. The research method was Research and Development (R&D) using ADDIE development models, namely: